Baseline results from the EU28 EUROMOD (2011-2015) - Chrysa Leventi; Sanja Vujackov (University of Essex, Institute for Social and Economic Research (ISER), 2016)
This paper presents baseline results from the latest version of EUROMOD (version G3.0+), the tax-benefit microsimulation model for the EU-28. First, we briefly report the process of updating EUROMOD. We then present indicators for income inequality and risk of poverty using EUROMOD and discuss the main reasons for differences between these and EU-SILC based indicators. We further compare EUROMOD indicators across countries and over time between 2011 and 2015 (or 2014 in some cases). Finally, we provide estimates of marginal effective tax rates (METR) for all 28 EU countries in order to explore the effect of tax and benefit systems on work incentives at the intensive margin. Throughout we highlight both the potential of EUROMOD as a tool for policy analysis and the caveats that should be borne in mind when using it and interpreting results. This paper updates the work reported in EUROMOD Working Paper EM18/2014.
Keywords: C15; H24; H31; H55; I3; 330; microsimulation; redistribution; tax-benefit system; poverty; inequality; work incentives